2021
DOI: 10.1055/s-0041-1733938
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Ophthalmology Fellowship Interviews: Perceptions of U.S. Ophthalmology Fellowship Applicants in 2020

Abstract: Objective This study aimed to evaluate the experiences and preferences of ophthalmology fellowship applicants utilizing a virtual interview format. Design Present study is a cross-sectional study. Subjects All fellowship applicants to Wills Eye Hospital during 2020 to 2021 application cycle were included. Methods A nonvalidated, online survey was conducted, and surveys were distributed at the conclusion of the interview process after rank list submission. Main Outcome Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(13 citation statements)
references
References 23 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…This is further supported by the literature, where difficulty assessing program fit is the most commonly reported drawback of the virtual interview. 1,2,4,6,[12][13][14] Meanwhile, our study demonstrated two major strengths of in-person interviews. The largest strength was increased exposure to the details of the program structure, a finding which mirrored the largest weakness of virtual formats.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…This is further supported by the literature, where difficulty assessing program fit is the most commonly reported drawback of the virtual interview. 1,2,4,6,[12][13][14] Meanwhile, our study demonstrated two major strengths of in-person interviews. The largest strength was increased exposure to the details of the program structure, a finding which mirrored the largest weakness of virtual formats.…”
Section: Discussionmentioning
confidence: 75%
“…Still, virtual interviews remain the predominant format for residency and fellowship interviews despite limited understanding of how this platform affects the interview process. 1 According to a 2021 survey study by Patel et al, applicants were generally satisfied with virtual interviews due to reduced costs and increased ability to attend a greater number of interviews. 1 Other studies surveying applicants, interviewers, and committee members within various specialties demonstrated more equivocal results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Limitations of this study include a small sample size, despite an acceptable survey response rate similar to other studies cited here. 5,7,9 While participants were comprised of retina fellowship applicants to only three programs, this likely represents a majority of retina fellowship applicants within these two interview cycles given the significant overlap of applicants between programs. However, it may not be generalizable to ophthalmology fellows within other subspecialties.…”
Section: Discussionmentioning
confidence: 99%
“…Patel et al studied the perceptions of virtual interviewees shortly after the AUPO mandate and reported similar findings, including reduced cost, ability to attend more interviews, and overall high satisfaction but limited exposure to the program culture. 7 Another survey of a cohort of virtual retina fellowship interviewees additionally reported increased difficulty representing themselves over a virtual platform, compared with the same survey of in-person applicants from the year prior to the mandate. 2 …”
mentioning
confidence: 99%